Teacher preparedness for transformative education in the intermediate phase: Insights from Eastern Cape, South Africa - Matthew Damilola Omojemite (Interdisciplinary Journal of Education Research)
Transformative education, informed by Sustainable Development Goal 4, emphasises inclusive, equitable, and quality education through learner-centred, critical, and reflective pedagogies. This study investigated the readiness of intermediate phase teachers in the Eastern Cape Province of South Africa to implement transformative education. The study assesses the level of teacher readiness and identifies the challenges, opportunities, and facilitating factors affecting the operationalisation of transformative education. A descriptive survey research design was adopted for this study. The population consisted of 5,200 intermediate phase teachers in selected urban and rural schools in the Eastern Cape. One hundred teachers were selected from 20 schools using stratified random sampling to obtain representation across geographic and socio-economic environments. A questionnaire was used and validated by experts, and the reliability was determined, obtaining a Cronbach's alpha coefficient of 0.87. The data collected were analysed using descriptive statistics. Findings revealed that teachers were highly aware of and committed to the values of transformative education but were constrained in implementation by factors such as poor infrastructure, a high student-to-teacher ratio, lack of internet resources, and insufficient time for professional development. Socio-cultural constraints and language diversity posed delivery difficulties. Based on these findings, it was recommended that stakeholders in education focus on investing in infrastructure, crafting professional development programmes, and promoting local action to create the enabling environments within which transformative education can develop. Similarly, there should be policy reforms that are sensitive to contextual realities, reforms that strengthen teachers' power by supporting them through positive leadership and learning networks.